Managing Chaos: Bridging the cultural divide between engineers and scientists working within the life sciences - Killcoyne, Sarah; Boyle, John (Computing in science & engineering, 2019)
Within the rather chaotic atmosphere of scientific research the adoption of a software process, and the structured development of software, can be out of place. It is important to realize that the advancement of science is paramount, and so a balance must always be drawn between the cost and the benefit of the introduction of process into a research environment. This necessity presents a unique set of challenges to software development within the life sciences. These unique challenges are due to the cultural disconnect between life science research and software engineering. This paper outlines these challenges, and also discusses the software process used by the Institute for Systems Biology (ISB) to address them.